THE NONLINEAR RELATION BETWEEN BIOFUELS AND FOOD PRICES - Cruz Aké, Salvador (Investigación Económica, 2017)
This paper analyzes the relationship between the production of agricultural foods (cereals and vegetable oils) and the production of energy by using food. The observed increase in economic activities that use energy has had an impulse in the energy industry with higher prices. These prices make profitable the biofuel production, and this encourage the use of cereals for biofuel production, affecting the whole food chain. This research demonstrates that the agricultural foods and energy production system has been in place at least since 2000 and that it remains active or latent depending on the price of energetics. The paper also shows that the temperature variations do not lead the system to an adjustment. To do, this research uses the econometric technique of Dynamic Conditional Correlation, and a new tool, phase synchronization. The use of the latter avoid making assumptions on the distribution or stability of the involved variables.